Understanding Individual Barriers to HIV Testing Among Undergraduate University Students: Results From a Cross-Sectional Study in Italy - Licata, Francesca; Angelillo, Silvia; Nobile, Carmelo Giuseppe Angelo; Di Gennaro, Gianfranco; Bianco, Aida (Frontiers in Medicine, 2022)
Background: In Europe during 2019, just over half of those with HIV were diagnosed at a late stage of infection. Even though HIV testing is crucial for all strategies related to care, prevention and treatment of HIV/AIDS, we hypothesized that it is less practiced among university students, and, therefore, this study aimed to assess the uptake and factors associated with HIV testing in Southern part of Italy. Methods: A cross-sectional study was conducted from 1st to 31st July 2020 among undergraduate university students aged 18-29 years. Data were collected through an anonymous online questionnaire and included questions on socio-demographic and sexual history characteristics, knowledge and attitudes towards HIV infection, sexual and testing behaviors, and sources of information about HIV. Findings: Among 1007 students, 41.5% and 54.7% knew that in Italy the test for early detection of HIV infection has not to be prescribed by a physician and that it is provided to anyone free of charge, respectively. Only 16.2% of the eligible students reported having ever tested for HIV and a very similar proportion (17.8%) was displayed among those who reported risky sexual behaviors. The multiple logistic regression analysis results indicated that the strongest predictor of HIV testing was attending medical or life sciences majors. Interpretation: The uptake of HIV testing was low among Italian university students. Effective strategies to increase HIV testing and diagnoses have to aim at overarching individual barriers, such as lack of knowledge about information around the test itself.